Spaces:
Running
Running
Update app.py
Browse files
app.py
CHANGED
@@ -105,9 +105,9 @@ def calculate_probabilities(A, B, C, AB, AC, BC, ABC, U):
|
|
105 |
"P(B | A) (T. Bayes)": f"{P_B_given_A_bayes:.2%} (Teorema de Bayes: (P(A | B) * P(B)) / P(A)) = ({PA_given_B:.4f} * {P_B:.4f} / {P_A:.4f})",
|
106 |
"P(C | A) (T. Bayes)": f"{P_C_given_A_bayes:.2%} (Teorema de Bayes: (P(A | C) * P(C)) / P(A)) = ({PA_given_C:.4f} * {P_C:.4f} / {P_A:.4f})",
|
107 |
"P(C | B) (T. Bayes)": f"{P_C_given_B_bayes:.2%} (Teorema de Bayes: (P(B | C) * P(C)) / P(B)) = ({PB_given_C:.4f} * {P_C:.4f} / {P_B:.4f})",
|
108 |
-
"P(A ∪ B)": f"{P_A_union_B:.2%} (P(A) + P(B) - P(A ∩ B)) = ({P_A:.4f} + {P_B:.4f} - {P_AB:.4f})",
|
109 |
-
"P(A ∪ C)": f"{P_A_union_C:.2%} (P(A) + P(C) - P(A ∩ C)) = ({P_A:.4f} + {P_C:.4f} - {P_AC:.4f})",
|
110 |
-
"P(B ∪ C)": f"{P_B_union_C:.2%} (P(B) + P(C) - P(B ∩ C)) = ({P_B:.4f} + {P_C:.4f} - {P_BC:.4f})",
|
111 |
"P(A ∪ B ∪ C)": f"{P_A_union_B_union_C:.2%} (P(A) + P(B) + P(C) - P(A ∩ B) - P(A ∩ C) - P(B ∩ C) + P(A ∩ B ∩ C)) = ({P_A:.4f} + {P_B:.4f} + {P_C:.4f} - {P_AB:.4f} - {P_AC:.4f} - {P_BC:.4f} + {P_ABC:.4f})",
|
112 |
"U (Universal Set)": total,
|
113 |
"Complemento de A U B U C": U - (A + B + C - AB - AC - BC + ABC)
|
|
|
105 |
"P(B | A) (T. Bayes)": f"{P_B_given_A_bayes:.2%} (Teorema de Bayes: (P(A | B) * P(B)) / P(A)) = ({PA_given_B:.4f} * {P_B:.4f} / {P_A:.4f})",
|
106 |
"P(C | A) (T. Bayes)": f"{P_C_given_A_bayes:.2%} (Teorema de Bayes: (P(A | C) * P(C)) / P(A)) = ({PA_given_C:.4f} * {P_C:.4f} / {P_A:.4f})",
|
107 |
"P(C | B) (T. Bayes)": f"{P_C_given_B_bayes:.2%} (Teorema de Bayes: (P(B | C) * P(C)) / P(B)) = ({PB_given_C:.4f} * {P_C:.4f} / {P_B:.4f})",
|
108 |
+
"P(A ∪ B)": f"{P_A_union_B:.2%} (P(A) + P(B) - P(A ∩ B)) = ({P_A:.4f} + {P_B:.4f} - {P_AB:.4f}) = (A + B - A ∩ B) / U = ({A} + {B} - {AB}) / {U}",
|
109 |
+
"P(A ∪ C)": f"{P_A_union_C:.2%} (P(A) + P(C) - P(A ∩ C)) = ({P_A:.4f} + {P_C:.4f} - {P_AC:.4f}) = (A + C - A ∩ C) / U = ({A} + {C} - {AC}) / {U} ",
|
110 |
+
"P(B ∪ C)": f"{P_B_union_C:.2%} (P(B) + P(C) - P(B ∩ C)) = ({P_B:.4f} + {P_C:.4f} - {P_BC:.4f}) = (B + C - B ∩ C) / U = ({B} + {C} - {BC}) /{U} ",
|
111 |
"P(A ∪ B ∪ C)": f"{P_A_union_B_union_C:.2%} (P(A) + P(B) + P(C) - P(A ∩ B) - P(A ∩ C) - P(B ∩ C) + P(A ∩ B ∩ C)) = ({P_A:.4f} + {P_B:.4f} + {P_C:.4f} - {P_AB:.4f} - {P_AC:.4f} - {P_BC:.4f} + {P_ABC:.4f})",
|
112 |
"U (Universal Set)": total,
|
113 |
"Complemento de A U B U C": U - (A + B + C - AB - AC - BC + ABC)
|